2022
DOI: 10.1002/ccd.30328
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the incidence of radial artery occlusion using different introducer sheaths and hemostasis techniques

Abstract: Background: Radial artery occlusion (RAO) remains one of the most important complications of transradial access (TRA). Despite the identification of multiple predictors, the interaction between these predictors on the occurrence of RAO has not been evaluated.Methods: Consecutive patients undergoing TRA coronary angiography (CA) or percutaneous coronary intervention (PCI), were retrospectively analyzed to compare the effect of standard patent hemostasis using a one-bladder band versus twobladder band with simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The PRISMA flow diagram for study search and selection is shown in Figure 1 . Of the 316 citations screened, a total of 6 studies, including 6793 patients, were identified and included in the final analysis [ 12 , 23 , 24 , 25 , 26 , 27 ]. Details on the search strategy are reported in the Supplementary Materials .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PRISMA flow diagram for study search and selection is shown in Figure 1 . Of the 316 citations screened, a total of 6 studies, including 6793 patients, were identified and included in the final analysis [ 12 , 23 , 24 , 25 , 26 , 27 ]. Details on the search strategy are reported in the Supplementary Materials .…”
Section: Resultsmentioning
confidence: 99%
“…Coronary angiography alone was performed in one study [ 9 ], PCI following coronary angiography was performed in a variable proportion of patients ranging from 15.6% to 58.7% across 4 studies [ 23 , 25 , 26 , 27 ], while no information was available in one study [ 24 ]. Patients presenting with acute coronary syndrome were excluded in two studies [ 12 , 26 ], data regarding the clinical syndrome were reported in two studies [ 23 , 25 ], with the proportion of acute coronary syndrome ranging from 30.2% to 88.7%, and no information was available in 2 studies [ 24 , 27 ]. The best recommendations for the detection and prevention of RAO were followed in all included studies [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patel et al report that the incidence of RAO after 6 French radial access was less in the two‐bladder band with simultaneous ipsilateral ulnar compression (1.0%) versus the one‐bladder band group (4.2%, p = 0.009) 3 . Of those that received the two‐bladder band, the incidence of RAO was similar with the use of the 6 French versus 7 French slender introducers (1.0% vs. 0.9%, p = 0.9).…”
Section: Author Journal Date Study Design Study Hypothesis Finding Co...mentioning
confidence: 99%
“…In this issue of Catheterization and Cardiovascular Interventions , Patel et al report a study comparing patent hemostasis with a one‐bladder compression band (TR band) versus a novel two‐bladder compression band (Vasoband, VASOInnovations Inc.) that provides simultaneous ipsilateral ulnar artery compression. They observed sequential cohorts of 1592 patients treated with the single‐bladder band over 16 months and 427 patients treated with the two‐bladder band over the next 8 months 3 The investigators further compared results with the two‐band device when radial access employed 6 French versus 7 French Terumo Slender introducer sheaths.…”
Section: Author Journal Date Study Design Study Hypothesis Finding Co...mentioning
confidence: 99%